Surgery with locking plate or hemiarthroplasty versus nonoperative treatment of 3–4-part proximal humerus fractures in older patients (NITEP): An open-label randomized trial - Launonen, Antti P.; Sumrein, Bakir O.; Reito, Aleksi; Lepola, Vesa; Paloneva, Juha; Berg, Hans E.; Felländer-Tsai, Li; Kask, Kristo; Rahnel, Timo; Tootsi, Kaspar; Märtson, Aare; Jonsson, Kenneth B.; et al. (PLoS medicine, 2023)
Proximal humerus fractures (PHFs) are common fractures, especially in older female patients. These fractures are commonly treated surgically, but the consensus on the best treatment is still lacking. The primary aim of this multicenter, randomized 3-arm superiority, open-label trial was to assess the results of nonoperative treatment and operative treatment either with locking plate (LP) or hemiarthroplasty (HA) of 3- and 4-part PHF with the primary outcome of Disabilities of the Arm, Shoulder, and Hand (DASH) at 2-year follow-up. In this study, no benefit was observed between operative treatment with LP or HA and nonoperative treatment in displaced 3- and 4-part PHFs in patients aged 60 years and older. Further, we observed a high rate of complications related to operative treatments.